IMPLEMENTASI BAHAN AJAR MATA KULIAH PEMBELAJARAN BILINGUAL BERBASIS MODEL PJBL DALAM MENDUKUNG OUTCOME BASED EDUCATION - Betty Simanjuntak, Eva; Simbolon, Naeklan; Simanihuruk, Lidia; Pauli Sirait, Albert (Universitas Negeri Medan, 2024)
This research aims to describe the implementation of ESP-based PJBL-oriented Bilingual Learning courses and to determine the influence of Bilingual Learning teaching materials on student learning outcomes. This type of research is Mixed Research method (MMR). The average N-Gain Score is 0.3846 or 38.46%, which falls into the “medium” category. This shows an increase in students' bilingual abilities. The minimum N-Gain value was -0.94 (-93.75%) and the maximum was 0.83 (82.69%), indicating large variations in implementation effectiveness among students. The results of the significance test show a calculated t value of 5.461 with a significance value of 0.000 (p < 0.05), which means that there is a significant influence from the use of teaching materials for the PjBL-oriented ESP-Based Bilingual Learning course on students' learning outcomes in bilingual learning courses.